Advancing calibration techniques for accurate micro and nanoflow measurements - Batista, E.; Martins, Rui F.; Silverio, Vania; Godinho, Isabel (Frontiers in Nanotechnology, 2025)
The lack of established protocols and standards for calibrating flow measuring instruments operating in the microflow range raises concerns about the reliability and precision of such measurements results. This work focuses on developing and improving innovative calibration methodologies to enhance the accuracy of microflow and nanoflow measurements. The gravimetric method already implemented at IPQ from 120 μL/h to 2000 mL/h was used and improved for low flow rates down to 10 μL/h. Additionally, three other optical methods were developed to calibrate micro/nano flows in a non-intrusive way: the interferometric, pending drop and front track. The methodology best suited for each specific flow instrument (e.g., syringe pumps and flow meters) and each for measurement range, with the lowest uncertainty, was successfully identified during this work. Also, it was possible to increase the measuring range of the Portuguese Institute for Quality–Volume and Flow Laboratory (IPQ-LVC) down to 5 nL/min (0.3 μL/h) with a 3% target uncertainty (k = 2). This was not only achieved but improved further with the interferometric method, where measurements were performed down to 1.6 nL/min (0.1 μL/h) with 2% uncertainty (k = 2). Furthermore, this method was external validated by a comparison performed under the EURAMET project 1508. The methodologies here described were the basis of the development of EURAMET guide cg 27 - Guidelines for the Calibration of Drug Delivery Devices and Infusion Device Analysers. This document provides standardized procedures for testing microflow and nanoflow instruments aiming to improve the accuracy and comparability of measurement results.